Keanekaragaman Vegetasi Rawa Di Kecamatan Tanjung Lago - Siti Indah Oktaviani; Didi Jaya Santri; Endang Dayat (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2016)
Oktaviani, et al. Vegetation Diversity of Swamp in Tajung Lago District. JLSO 5(2):198-207. The study aims to determine the vegetation diversity of swamp ecosystems in the district of Tanjung Lago. The study was conducted from June to July 2011. Theanalysis is using squares method, and quantitative data analysis was conducted to measure the value of density, dominance, frequency, importance and diversity index of each type of plant. The results showed that the vegetation in the swamp consists of 16 genus and 21 species dominated by Pteridophyta and Spermatophyta. The value of vegetation diversity (2.0680), where the higher the number, the higher the index type of diversity of a kind. Such characteristics are caused by environmental influences such as organic matter content and low pH and factors derived by human intervention.